"Cogito, Ergo Sum": Proof or Petitio?. Issue 3 (19th May 2022) - Dicker, Georges
ABSTRACT: E. M. Curley has said that Descartes' cogito, ergo sum "is as obscure on examination as it is compelling at first glance." Why should that be? Maybe because the cogito raises so many textual and interpretive questions. Is it an argument or an intuition? If it is an argument, does it require an additional premise? Is it best interpreted as a "performance?" Is it best seen as the discovery that any reason proposed for doubting its success entails the meditator's existence? And so on. But all these questions typically arise in the wake of worries about the cogency of the cogito when it is treated as an argument and worded in its canonical form, "I think, therefore I exist." In this essay, I focus on what I take to be the most fundamental reason for questioning the cogito 's cogency when it is so treated—namely that the "I" in its premise is question-begging. I distinguish that reason from other reasons that are sometimes conflated with it, and I argue that it is not a good reason. I then comment on some of the questions mentioned above in light of my defense of the cogito seen in that traditional way.